Rare Case of an Epithelial Cyst in an Intrapancreatic Accessory Spleen Treated by Robot-Assisted Spleen Preserving Distal Pancreatectomy - Willemijn P. M. van Dijck; Vincent P. Groot; Lodewijk A. A. Brosens; Jeroen Hagendoorn; Inne H. M. Borel Rinkes; Maarten S. van Leeuwen; I. Quintus Molenaar (Case Reports in Gastrointestinal Medicine)
Epithelial cyst in an intrapancreatic accessory spleen (ECIPAS) is exceedingly rare with only 57 cases reported since the first publication in 1980. Comprehensive clinical and diagnostic features remain to be clarified. We present a case of ECIPAS in a 21-year-old Philippine woman who was admitted with right upper quadrant abdominal pain. A cystic lesion in the pancreatic tail was discovered and evaluated by computed tomography and magnetic resonance images. Based on clinical and radiological features a solid pseudopapillary neoplasm was suspected. The patient underwent robot-assisted spleen preserving distal pancreatectomy. Pathological evaluation revealed a 26 mm intrapancreatic accessory spleen with a 16 mm cyst, lined by multilayered epithelium in the tail of the pancreas. The postoperative course was uneventful. Differentiating ECIPAS from (pre)malignant cystic pancreatic neoplasms based on clinical and radiological features remains difficult. When typical radiological signs can be combined with scintigraphy using Technetium-99m labelled colloid or Technetium-99m labelled erythrocytes, which can identify the solid component of the lesion as splenic tissue, it should be possible to make the right diagnosis noninvasively. When pancreatectomy is inevitable due to symptoms or patient preference, minimally invasive laparoscopic or robot-assisted spleen preserving distal pancreatectomy should be considered.